2009
DOI: 10.1523/jneurosci.2525-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

Emx1-Lineage Progenitors Differentially Contribute to Neural Diversity in the Striatum and Amygdala

Abstract: In the developing mammalian basal telencephalon, neural progenitors from the subpallium generate the majority of inhibitory medium spiny neurons (MSNs) in the striatum, while both pallial- and subpallial-derived progenitors contribute to excitatory and inhibitory neuronal diversity in the amygdala. Using a combination of approaches, including genetic fate mapping, cell birth dating, cell migration assays, and electrophysiology, we find that cells derived from the Emx1 lineage contribute to two distinct neurona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(72 citation statements)
references
References 72 publications
(107 reference statements)
3
69
0
Order By: Relevance
“…5F-J We have also deleted COUP-TF alleles in SVZ cells using Emx1-Cre mice (Gorski et al, 2002;Bovetti et al, 2013). Emx1 and Emx1-cre are not only expressed in almost all progenitors in neocortical and septal VZ/SVZ (Gorski et al, 2002), but are also expressed in a large number of progenitors in the LGE and CGE (Cocas et al, 2009;Waclaw et al, 2009 Fig. S10K,L).…”
Section: Few Coup-tfii+ Cells Exist In the Adult Svz-rms-ob Pathwaymentioning
confidence: 99%
“…5F-J We have also deleted COUP-TF alleles in SVZ cells using Emx1-Cre mice (Gorski et al, 2002;Bovetti et al, 2013). Emx1 and Emx1-cre are not only expressed in almost all progenitors in neocortical and septal VZ/SVZ (Gorski et al, 2002), but are also expressed in a large number of progenitors in the LGE and CGE (Cocas et al, 2009;Waclaw et al, 2009 Fig. S10K,L).…”
Section: Few Coup-tfii+ Cells Exist In the Adult Svz-rms-ob Pathwaymentioning
confidence: 99%
“…The migration of progenitors from ventral to dorsal germinative zones (Fishell et al, 1993), as well as in the dorsal to ventral direction (Willaime-Morawek et al, 2006;Cocas et al, 2009), could also contribute to the switch in the generation of neuronal subtypes in the embryonic telencephalon. Cocas et al (Cocas et al, 2009), for example, showed that Emx1-derived cells migrating from dorsal to ventral telencephalon contribute inhibitory medium spiny neurons in the striatum.…”
Section: Environmental Signals and Neuronal Plasticity In The Developmentioning
confidence: 99%
“…Cocas et al (Cocas et al, 2009), for example, showed that Emx1-derived cells migrating from dorsal to ventral telencephalon contribute inhibitory medium spiny neurons in the striatum. Therefore, neurotransmitter specification in the embryonic telencephalon seems to be a sum of early positional, intrinsic, information and the extrinsic signals coming from the actual environment.…”
Section: Environmental Signals and Neuronal Plasticity In The Developmentioning
confidence: 99%
“…Although embryonic development of the amygdala is poorly understood, a wide array of approaches used in a number of studies, including fate mapping, migration assays and genetic knockout studies, are assembling an interesting picture specifically regarding the development of the fear circuits in the amygdala [141,142,143,144]. Several transcription factors and genes are thought to be involved in regulating amygdala development and function, so any disruption of the function of one or more of these genes during development might impair the appropriate functional ensembles of neurons and synapses, which ultimately mediate fear and anxiety behaviors.…”
Section: Developmental Studies Of Amygdala Fear Circuits: Importance mentioning
confidence: 99%